The Impact of Market Orientation on Patient Safety Climate Among Hospital Nurses. (March 2016) - Weng, Rhay-Hung; Chen, Jung-Chien; Pong, Li-Jung; Chen, Li-Mei; Lin, Tzu-Chi
Improving market orientation and patient safety have become the key concerns of nursing management. For nurses, establishing a patient safety climate is the key to enhancing nursing quality. This study explores how market orientation affects the climate of patient safety among hospital nurses. We proposed adopting a cross-sectional research design and using questionnaires to collect responses from nurses working in two Taiwanese hospitals. Three-hundred and forty-three valid samples were obtained. Multiple regression and path analyses were conducted to test the study. Market orientation was defined as the combination of customer orientation, competitor orientation, and interfunctional coordination. Customer orientation directly affects the climate of patient safety. Although the findings only supported Hypothesis 1, competitor orientation and interfunctional coordination positively affected the patient safety climate through the mediating effects of hospital support for staff. Health care managers could encourage nurses to adopt customer-oriented perspectives to enhance their nursing care. In addition, to enhance competitor orientation, interfunctional coordination, and the patient safety climate, hospital managers could strengthen their support for staff members.